2013
DOI: 10.1016/j.foodchem.2012.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antihypertensive properties of liquid and solid state fermented lentils

Abstract: The effect of liquid (LSF) and solid state fermentation (SSF) of lentils for production of water-soluble fractions with antioxidant and antihypertensive properties was studied. LSF was performed either spontaneously (NF) or by Lactobacillus plantarum (LP) while SSF was performed by Bacillus subtilis (BS). Native lactic flora in NF adapted better than L. plantarum to fermentative broth and BS counts increased 4.0 logCFU/g up to 48 h of SSF. LSF water-soluble fractions had higher (P ≤ 0.05) free amino groups, GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
149
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(182 citation statements)
references
References 56 publications
(62 reference statements)
13
149
2
8
Order By: Relevance
“…This IC 50 value was lower than those reported for fermented products of soybean (80-360 µg/mL) [Pyo & Lee (35)] and lentils (180-200 µg/mL) [33]. The IC 50 value of the bioprocessed mixture corresponded to an intermediate value between the IC 50 values of bioprocessed QPM flour and bioprocessed common bean flour (0.0145 -358 µg/mL; Table 3), while the antioxidant activity of the bioprocessed mixture was similar to the antioxidant activity value of bioprocessed QPM flour [205.09 µmol trolox equivalent/g sample (dw); Table 3] and lower than bioprocessed common bean flour [227.33 µmol trolox equivalent/g sample (dw); Table 3].…”
Section: Angiotensin Converting Enzyme-inhibitory (Ace-i) Activity Ofcontrasting
confidence: 68%
See 1 more Smart Citation
“…This IC 50 value was lower than those reported for fermented products of soybean (80-360 µg/mL) [Pyo & Lee (35)] and lentils (180-200 µg/mL) [33]. The IC 50 value of the bioprocessed mixture corresponded to an intermediate value between the IC 50 values of bioprocessed QPM flour and bioprocessed common bean flour (0.0145 -358 µg/mL; Table 3), while the antioxidant activity of the bioprocessed mixture was similar to the antioxidant activity value of bioprocessed QPM flour [205.09 µmol trolox equivalent/g sample (dw); Table 3] and lower than bioprocessed common bean flour [227.33 µmol trolox equivalent/g sample (dw); Table 3].…”
Section: Angiotensin Converting Enzyme-inhibitory (Ace-i) Activity Ofcontrasting
confidence: 68%
“…still remain in raw QPM and common beans, which can result in a minor DH than the bioprocessed samples, while soaking and cooking treatments applied previously to the fermentation, can be promoted leaching and/or inactivation of antinutritional factors, increasing the DH of the samples. During fermentation step also occurs elimination of antinutritional factors caused by the action of the fungus, while during the cooking step, proteins are denatured contributing both steps to increasing the DH [33].…”
Section: Degree Hydrolysis (Dh) Of Bqpmf and Bcbfmentioning
confidence: 99%
“…8 GABA is a non-protein amino acid, known as one of the main inhibitory neurotransmitters in the sympathetic nervous system, and it plays an important role in cardiovascular functions. 15 Tocopherol is the major lipophilic fraction of whole grain rice and its health-beneficial potential has been proposed. 16 In the present study, all the rice kefir powders showed the amount of TPC higher than non-fermented brown rice reported on previous work.…”
Section: Discussionmentioning
confidence: 99%
“…During fermentation, proteolytic enzymes hydrolyze complexes of phenolics into soluble-free phenols and other simpler and biologically more active ones [14,15]. The bioconversion of the conjugated forms of phenolic compounds into their free forms during fermentation improves their health-linked functionality as antioxidants [16]. However, increasing the fermentation time might allow the microorganisms to use those available compounds as substrates for their growth, thus reducing the sample concentration.…”
Section: Response Surface Methodologymentioning
confidence: 99%